PENGARUH GAYA KEPEMIMPINAN DEMOKRASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DIMEDIASI OLEH BUDAYA ORGANISASI DI UPTD PUSKESMAS BANTARAN KECAMATAN BANTARAN KABUPATEN PROBOLINGGO - Puja Agshari Retnaningtyas; Sri Hadiati; Jamal Abdul Nasir (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2022)
The purposes of this study are 1) To test and analyze Leadership Style and Work Discipline have a significant effect on organizational culture 2) To test and analyze Leadership Style and Work Discipline have a significant effect on Employee Performance 3) To test and analyze Organizational Culture has a significant effect on Employee Performance 4) To test and analyze Leadership Style has a significant effect on Employee Performance 5) To test and analyze Work Discipline has a significant effect on Employee Performance at UPTD Puskesmas Banataran Probolinggo Regency. This research is a quantitative research with an approach to the research method of explanation. The sample used was 50 patient respondents in June 2022 at the UPTD Puskesmas Bantaran, Probolinggo Regency with a total sampling. The analysis used is path analysis. By using SPSS 25 calculation and Sobel MediationTest. The results showed that 1) Leadership Style had an effect on organizational culture 2) Work Discipline had no significant effect on organizational culture 3) Organizational Culture had a significant effect on employee performance 4) Leadership Style had no significant effect on employee performance 5) Work Discipline had no significant effect on performance employee.